2015
DOI: 10.1681/asn.2014010108
|View full text |Cite|
|
Sign up to set email alerts
|

High-Sensitivity Troponin T and N-Terminal Pro-B-Type Natriuretic Peptide (NT-proBNP) and Risk of Incident Heart Failure in Patients with CKD

Abstract: High-sensitivity troponin T (hsTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) strongly predict heart failure (HF) in the general population. However, the interpretation of levels of these biomarkers as predictors of HF is uncertain among patients with CKD. Here, we investigated whether hsTnT and NTproBNP are associated with incident HF among patients with CKD. In a prospective cohort analysis, we studied 3483 people with CKD in the Chronic Renal Insufficiency Cohort (CRIC) Study recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 51 publications
7
71
0
Order By: Relevance
“…LVH is likely a multifactorial process including known or unknown inflammatory and fibrotic mediators that were not measured in this investigation. We also adjusted for two markers of end organ damage, BNP and troponin T, and found that LVMI predicted HF independently of these powerfully prognostic biomarkers in CKD (24).…”
Section: Discussionmentioning
confidence: 99%
“…LVH is likely a multifactorial process including known or unknown inflammatory and fibrotic mediators that were not measured in this investigation. We also adjusted for two markers of end organ damage, BNP and troponin T, and found that LVMI predicted HF independently of these powerfully prognostic biomarkers in CKD (24).…”
Section: Discussionmentioning
confidence: 99%
“…6 Myocardial ischemia resulting from supply-demand mismatch may lead to low-level myocardial injury and regional wall motion abnormalities and may explain the association between elevated high-sensitivity cardiac troponin T and incident heart failure in patients with dd-ESRD without coronary artery disease. 13,14 Second, impaired global CFR may also reflect microvascular dysfunction resulting from arteriolar remodeling, 15 endothelial dysfunction, and/or increased extravascular resistance (i.e., left ventricular hypertrophy or interstitial fibrosis), all of which have been documented in patients with uremia 16 and may be contributors to subclinical myocardial ischemia and injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the European Prevention of Renal and Vascular Endstage Disease (PREVEND) study of over 1000 patients with CKD, elevations in NT pro-BNP and hs-TnT were significantly associated with cardiovascular events (defined as MI, ischaemic heart disease and coronary artery bypass grafting or percutaneous coronary angioplasty) 14. The 2015 CRIC study specifically evaluated for incident HF and found that patients with CKD in the highest quartiles of NT pro-BNP and hs-TnT had a nearly 10-fold and fivefold higher risk of incident HF, respectively 15. However, the use of these biomarkers in the clinical setting still remains controversial since there are no accepted cut-offsin the CKD population.…”
Section: Diagnosis Of Heart Failure In Patients With Kidney Diseasementioning
confidence: 99%